Efeito de preparações de produtos naturais (cravo da índia e tomate) e de um produto sintético na marcação de constituintes sangüineos com tecnécio-99m e na morfologia de hemácias isoladas de sangue de ratos wistar - Paoli, Severo de (2007)
There are strong interests in the evaluation of the biological effects of natural and synthetic products. Blood constituents labeled with technetium-99m (99mTc) are used in nuclear medicine. The aim of this work was to study the effects of Clove (Caryophyllus aromaticas L.) and OZE (preparation used in the Health Sciences) on the labeling blood constituents with 99mTc and on the morphologic red blood cells (RBC) and the action of an extract of tomato (TO) on the labeling of blood constituents Blood samples were incubated with clove or OZE or TO, stannous chloride and 99mTc. Plasma (P), blood cells (BC), insoluble fractions (IF) of plasma and blood cells were separated. The radioactivity was counted and percentage of radioactivity (%ATI) to each blood fraction was calculated. The shape and morphometric parameter (perimeter/area ratio) were evaluated in the studies with clove and OZE. Clove extract and OZE altered significantly (p<0.05) the %ATI of blood constituents and the shape of red blood cells. However, clove extract not altered the red blood cells perimeter/area ratio. The tomato extract used at the highest concentrations reduced significantly (p<0.05) the %ATI in IF-P, although this extract did not modify the radiolabeling on BC, neither the radioactivity fixation on IFBC. The results indicate that these chemical compounds would have oxidative/chelating actions